Longitudinal associations of plasma kynurenines and ratios with fatigue and quality of life in colorectal cancer survivors up to 12 months post-treatment - Holthuijsen, Daniëlle; van Roekel, Eline H.; Bours, Martijn J. L.; Ueland, Per M.; Breukink, Stéphanie O.; Janssen-Heijnen, Maryska L. G.; Keulen, Eric T. P.; Brezina, Stefanie; Gigić, Biljana; Peoples, Anita R.; Ulrich, Cornelia; Ulvik, Arve; et al. (International journal of cancer, 2024)
Fatigue is prevalent in colorectal cancer (CRC) survivors, impacting their health-related quality of life (HRQoL). Inflammation-induced activation of the kynurenine pathway may play a role in cancer-related fatigue and HRQoL, but evidence is scarce. Therefore, we aimed to investigate longitudinal associations of plasma tryptophan, kynurenines, and ratios with fatigue and HRQoL in CRC survivors up to 12 months post-treatment. Repeated measurements at 6 weeks, 6 months, and 12 months post-treatment were performed in 249 stage I-III CRC survivors. Plasma tryptophan and eight kynurenines were analyzed using liquid chromatography-tandem mass spectrometry (LC/MS-MS). Fatigue and HRQoL outcomes were evaluated using validated questionnaires. Confounder-adjusted linear mixed models were conducted to analyze longitudinal associations, with false discovery rate (FDR) correction. Higher tryptophan (Trp), kynurenic acid (KA), and xanthurenic acid (XA) concentrations, as well as a higher kynurenic acid-to-quinolinic acid ratio (KA/QA), were associated with less fatigue and better functioning, while a higher kynurenine-to-tryptophan ratio (KTR) and 3-hydroxykynurenine ratio (HKr) were associated with more fatigue and worse functioning. Finally, higher KA and XA concentrations and a higher KA/QA ratio were associated with a higher overall HRQoL summary score, while a higher HKr was associated with a lower overall HRQoL summary score. In conclusion, we observed that tryptophan and several kynurenines were longitudinally associated with fatigue and HRQoL in CRC survivors up to 12 months post-treatment. Future research is needed to validate our findings and explore the potential of the kynurenine pathway as intervention target for reducing fatigue and enhancing HRQoL after CRC treatment.
Gesehen am 18.11.2024
Veröffentlicht: 23 May 2024